Implementasi Metode Lean Ux User Interface Dan User Experience Pada Aplikasi Forum Group Discussion Charum - Wijaya, Alek; Al Fauzan, Muhammad Farhan; Syakti, Firamon; Putra, M.Soekarno (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Even though the internet is very important for education, currently there is a phenomenon in Indonesia which shows a high interest in internet use by all age groups. Indonesians spend more time on their cell phones than reading newspapers to read popular news. However, the use of social media often has negative content such as hoaxes, hate speech, pornography and violence. To overcome this problem, an FGD (Forum Group Discussion) application called Charum was established. Charum is designed as a group discussion platform for various topics, including programming, job vacancies, politics and games. This application makes it easy to search for topics, search for popular topics, and follow existing threads. In its development, this application uses the Lean UX method with three processes: think, make, and check. At the checking stage, usability testing and usability scales are carried out to ensure that the designs made can solve existing problems.